Consumer Behavior, Global Edition - Solomon, Michael R.; Russell, Cristel Antonia (Pearson International Content, 2023)
Consumer Behavior: Buying, Having, and Being, Global Edition covers all of the processes involved when we select, purchase, use or dispose of products, services, ideas or experiences. It investigates the many factors that affect our consumption choices (and non-choices), especially in the era of social media and the digital age. Since we're all consumers, many of the topics have both professional and personal relevance, making it easy to apply the theories outside of class. Featuring new co-author, Cristel Antonia Russell, the 14th Edition has been significantly revised to elevate its flow, focus, intentionality, freshness and attention to practice.